Comparison between High-Power Short-Duration and Conventional Ablation Strategy in Atrial Fibrillation: An Updated Meta-Analysis. (29th July 2022) - Li, Mohan; Ma, Yingxu; Lin, Qiuzhen; Huang, Yunying; Liu, Yaozhong; Tu, Tao; Liu, Qiming
Abstract : High-power short-duration (HPSD) setting during radiofrequency ablation has become an attempt to improve atrial fibrillation (AF) treatment outcomes. This study ought to compare the efficacy, safety, and effectiveness between HPSD and conventional settings. PubMed, Embase, and Cochrane Library were searched. Studies that compared HPSD and conventional radiofrequency ablation settings in AF patients were included while studies performed additional ablations on nonpulmonary vein targets without clear recording were excluded. Data were pooled with random-effect model. Efficacy endpoints include first-pass pulmonary vein isolation (PVI), acute pulmonary vein (PV) reconnection, free from AF, and free from atrial tachycardia (AT) during follow-up. Safety endpoints include esophagus injury rate and major complication rate. Effectiveness endpoints include complete PVI rate, total procedure time, PVI time, and PVI radiofrequency ablation (PVI RF) time. We included 22 studies with 3867 atrial fibrillation patients in total (2393 patients received HPSD radiofrequency ablation). Perioperatively, the HPSD group showed a higher first-pass PVI rate (risk ratio, RR = 1.10, P = 0.0001 ) and less acute PV reconnection rate (RR = 0.56, P = 0.0004 ) than the conventional group. During follow-up, free from AF (RR = 1.11, P = 0.16 ) or AT (RR = 1.06, P = 0.24 ) rate did not differ between HPSD and conventional groups 6-month postsurgery. However, the HPSD group showed both higher free from AF (RR = 1.17, P = 0.0003 ) and AT (RR = 1.11, P < 0.0001 ) rate than the conventional group 12-month postsurgery. The esophagus injury (RR = 0.99, P = 0.98 ) and major complications (RR = 0.76, P = 0.70 ) rates did not differ between the two groups. The HPSD group took shorter total procedure time (MD = − 33.71 95% CI: -43.10 to -24.33, P < 0.00001 ), PVI time (MD = − 21.60 95% CI: -25.00 to -18.21, P < 0.00001 ), and PVI RF time (MD = − 13.72, 95% CI: -14.45 to -13.00, P < 0.00001 ) than conventional groups while complete procedure rate did not differ between two groups (RR = 1.00, P = 0.93 ). HPSD setting during AF radiofrequency ablation has better effectiveness, efficacy, and similar safety compared with the conventional setting.